Classification of innovations in the agricultural sector as a precondition of forming marketing strategies of innovative development of agricultural enterpris - Y. Larina (Біоекономіка та аграрний бізнес, 2019)
Modern challenges and tasks facing Ukrainian enterprises of the agricultural sector require scientifically sound decisions on the formation and effective implementation of the strategy of innovative development of enterprises. Among the most common innovations in agriculture are: breeding achievements, chemical and biological products, advanced farming systems, the latest fertilizers and resource-saving technologies, economic development of agricultural machinery modification, marketing innovations, effective interaction between market players, the introduction of an Internet communications system etc.